The Stress Level and Coping Mechanism of Accredited Tour Guides in Bohol Amidst COVID-19 - Rodriguez, Gerald; Caneda, Rommel; Cagatin, Del Mark (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the stress levels and coping mechanisms of accredited tour guides in Bohol amidst the COVID-19 pandemic. Anchored on the Transactional Theory of Stress (Lazarus & Folkman, 1984) and the Conservation of Resources Theory (Hobfoll 1989; Hobfoll et al. 1996), the research employed a descriptive correlational design to analyze relationships among demographic profile, stress dimensions, and coping strategies. The respondents were 50 accredited tour guides listed by the Department of Tourism Region 7 and 50 family members who provided observational validation. Data were gathered through modified questionnaires based on the Pandemic Stress Questionnaire by Kujawa, A (2020), the IPHCPS questionnaire by Penedo, F (2020), and the Brief COPE Inventory (Carver, S 1997), and were analyzed using percentage, weighted mean, Spearman’s Rho, and Chi-square tests. Findings revealed that tour guides experienced high levels of stress across social, emotional/psychological, financial, educational/professional, and health domains, as confirmed by family members. Problem-focused and active emotional coping were frequently utilized, while avoidant/dysfunctional coping was least used. Significant relationships were identified between stress level and both problem-focused and avoidant/dysfunctional coping, but not with active emotional coping. No significant relationships were found between demographic profile and stress level, and only training showed a significant relationship with avoidant/dysfunctional coping. The study concludes that accredited tour guides faced substantial psychological and socio-economic strain, necessitating structured psychological interventions, counseling programs, resilience training, and alternative livelihood support. The study supports SDG 3 (Good Health and Well-Being), SDG 8 (Decent Work and Economic Growth), and SDG 11 (Sustainable Cities and Communities) by addressing mental health, employment disruption, and tourism resilience. Its sustainability impact lies in strengthening institutional, socio-economic, and community resilience through evidence-based psychological and policy interventions for tourism-dependent communities.
Keywords: Accredited tour guides, Bohol, Coping mechanisms, COVID-19, Descriptive correlational research, Stress level, Tourism industry, Transactional Theory of Stress